Savolitinib Induced Pathological Complete Response in Non-small Cell Lung Cancer with MET Amplification: A Case Report - Meng LU; Ran ZHANG; Baiwei LI; Haidi XU; Yongkuan GUO; Jian YOU; Bingsheng SUN (Chinese Journal of Lung Cancer)
Mesenchymal-epithelial transition factor (MET) gene mutation is a large class of mutations commonly seen in non-small cell lung cancer (NSCLC). MET mutation includes subtypes such as MET exon 14 skipping mutation (METex14m) and MET amplification (METamp). For advanced NSCLC with METex14m, Savolitinib has a high sensitivity as a member of tyrosine kinase inhibitors (TKIs). METamp is a relatively rare genetic mutation type which can serve as a driver gene to mediate primary and later acquired drug resistance of epidermal growth factor receptor (EGFR)-TKIs. For advanced NSCLC with secondary METamp, EGFR-TKIs combined with MET-TKIs are usually used in clinical treatment, while the optimal treatment strategy for advanced NSCLC with primary METamp has not yet been determined. For locally advanced NSCLC patients with positive driver gene mutations such as EGFR, anaplastic lymphoma kinase (ALK) fusion and METex14m, there have been relevant cases reported that neoadjuvant targeted therapy could achieve a good prognosis, but there have been no cases of neoadjuvant targeted therapy for locally advanced NSCLC patients with METamp. This report describes a case of a locally advanced NSCLC patient with dual driver gene mutations (EGFR L858R combined with primary METamp), the tumor did not shrink after 1 month of Gefitinib monotherapy, but significantly subsided after 4 months of Savolitinib monotherapy. After radical surgery, the pathological results proved pathological complete response (pCR) of the tumor, and the patient had a good response to postoperative continual Savolitinib treatment, with no recurrence nor metastasis observed to date. This case reports the feasibility and effectiveness of neoadjuvant targeted therapy for locally advanced NSCLC with primary METamp, aiming to provide effective reference for perioperative treatment of locally advanced NSCLC with primary METamp.